2003
DOI: 10.1144/gsl.sp.2003.207.11
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical evaluation of East Sirte Basin (Libya) petroleum systems and oil provenance

Abstract: With cumulative reserves exceeding 23 gigabarrels oil recoverable (GBOR), the East Sirte Basin is a prolific oil province hosting supergiants such as the Amal, Augila-Nafoora and Sarir fields. Production from Precambrian-Oligocene reservoirs yields low sulphur and often highly waxy oils.The Late Mesozoic-Cenozoic Agedabia and older Hameimat, Maragh and Sarir troughs provide the main structural features of the habitat and control hydrocarbon prospectivity. Paleogene subsidence has facilitated the generative pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 11 publications
1
28
1
Order By: Relevance
“…The majority of reserves lie in fluvial sands below Triassic salt and are Palaeozoic-sourced. There are also major reserves at this level in the Sirt Basin, sourced stratigraphically downward from Cretaceous source rocks (Burwood et al 2003). Imaging of undrilled traps below shifting sand dunes and salt is a critical-technology technique that has led to considerable recent success (Drummond et al 2003).…”
Section: Triassic and Early Jurassic In Interior Sag And Fracture Basinsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of reserves lie in fluvial sands below Triassic salt and are Palaeozoic-sourced. There are also major reserves at this level in the Sirt Basin, sourced stratigraphically downward from Cretaceous source rocks (Burwood et al 2003). Imaging of undrilled traps below shifting sand dunes and salt is a critical-technology technique that has led to considerable recent success (Drummond et al 2003).…”
Section: Triassic and Early Jurassic In Interior Sag And Fracture Basinsmentioning
confidence: 99%
“…In the Sirt Basin (Burwood et al 2003), which is the predominant hydrocarbon province within the class, the productive stratigraphic interval extends downward stratigraphically to include the important Albian sandstone play (Gras & Thusu 1998). Other basins in this class include the Gabes Basin of Tunisia and the interior rift basins of Sudan and Niger.…”
Section: Late Cretaceous and Palaeogene In Interior Fracture Basinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main source kitchen supplying the Concession 96 fields is located to the NW of As Sarah in the deepest portion of the Maragh Trough. Burwood (1996) showed that oil generation may have started as early as the Late Cretaceous. Significant expulsion of hydrocarbons however did not occur until Oligocene to Early Miocene times (Fig.…”
Section: Source Rocks and Chargingmentioning
confidence: 99%
“…The Upper Cretaceous -Lower Tertiary succession above the principal source rocksthe Lower Sirt or (Rakb Gamma) shales, which consist of more than 6,000 ft of tight lime mudstones, claystones and marls overlain by evaporiteshas prevented major vertical migration of hydrocarbons in the Maragh Trough. As the Lower Triassic lacustrine bituminous shale (PUC-A: Arratia, 2000;Schrank, 2000) and the Cretaceous Rakb Gamma shales are still within the oil window and are expelling hydrocarbons (Burwood et al, 1996), migration continues to takes place along faults or carrier beds filling structures or traps with good reservoir properties (Fig. 12).…”
Section: Source Rocks and Chargingmentioning
confidence: 99%